Excesso de peso e consumo de alimentos marcadores de dieta saudável e não saudável entre adultos de Cuiabá-MT, VIGITEL 2014 - Durante, Gabriela Dalcin (2016)
Overweight is an important risk factor for the development of non- communicable chronic diseases. The adult population of Cuiabá, capital of the state of Mato Grosso, has stood out for the high prevalence of overweight and, especially obesity, in both genders. The determinants of overweight are a complex set of biological, environmental and behavioral factors, such as sedentarism and inadequate eating habits, which inter-relate and potentiate each other. Objective: To analyze the prevalence of overweight and associated factors and the healthy and unhealthy food consumption of diet markers among adult of Cuiabá- MT. Methods: A cross-sectional, population-based study with data from the Surveillance System of Risk Factors and Protection for Chronic Diseases by Telephone Survey (VIGITEL) was conducted. A total of 1,005 adults aging from 20 to 59, residents of Cuiabá in 2014 were included. The dependent variable is overweight (Body Mass Index ≥ 25 Kg/m2 ). The explanatory variables are sociodemographic variables, healthy and unhealthy consumption markers, morbidity and lifestyle variables. In the data analysis, descriptive analysis of data, bivariate analysis through the chi-square test (Rao-Scott) and multiple logistic regression by hierarchical blocks were used. The explanatory variables which remained with p<0.05, were maintained in the final multiple model and considered to be associated with overweight. The data were analyzed by the software Stata, version 13, using the survey command. Results: In the analysis of overweight and associated factors among women, it was verified that most of the women were classified as overweight (53.2%). In the bivariate analysis schooling from 0 to 4 and from 5 to 8 years of schooling; living with a partner; being a former smoker; not having exercised in the three months prior to the interview; regular consumption of fruit and vegetable; infrequent consumption of sweets; presenting hypertension, diabetes or dyslipidemia; self- evaluate health as bad; and be between the ages of ≥ 30 years were associated with overweight in women. In the multiple analysis of logistic regression in hierarchic blocks, women with lower schooling (0 to 4 years of schooling), living with their partner, presenting hypertension and aged ≥ 30 years were associated with overweight in women. In the analysis of food consumption markers stratified by gender, there was a higher regular consumption of fruit and vegetables among women (p=0.01), among those with higher schooling and white race, and higher consumption of beans among men (p=0.04). The consumption of meats with excess fat was higher among men (p<0.01) and the regular consumption of sweets (p=0.02) and replacement of main meals for snacks (p=0.01) among women, both directly associated with schooling. Conclusions: Higher prevalence of overweight in women was associated with socioeconomic conditions, presence of morbidities and age. Significant differences were observed in food consumption between genders. Nutritional assistance and health education activities are useful strategies for this population.